What do we know about maternal and perinatal mortality and morbidity audits in sub-Saharan Africa? A scoping literature review. Issue 3 (19th July 2019) - Lusambili, Adelaide; Jepkosgei, Joyline; Nzinga, Jacinta; English, Mike
Abstract : Purpose: The purpose of this paper is to provide a situational overview of the facility-based maternal and perinatal morbidity and mortality audits (MPMMAs) in SSA, their current efficacy at reducing mortality and morbidity rates related to childbirth. Design/methodology/approach: This is a scoping literature review based on the synthesis of secondary literature. Findings: Not all countries in SSA conduct MPMMAs. Countries where MPMMAs are conducted have not instituted standard practice, MPMMAs are not done on a national scale, and there is no clear best practice for MPMMAs. In addition, auditing process of pediatrics and maternal deaths is flawed by human and organizational barriers. Thus, the aggregated data collected from MPMMAs are not adequate enough to identify and correct systemic flaws in SSA childbirth-related health care. Research limitations/implications: There are a few published literature on the topic in sub-Saharan Africa. Practical implications: This review exposes serious gaps in literature and practice. It provides a platform upon which practitioners and policy makers must begin to discuss ways of embedding mortality audits in SSA in their health systems as well as health strategies. Social implications: The findings of this paper can inform policy in sub-Saharan Africa that could lead toward better outcomes in health and well-being. Originality/value: The paper is original.